Vocational High School Students’ Creative Thinking Skills Comparison Between Project-Based Learning and Problem-Based Learning Instructional Process in Software Development Subjects - Herlambang, Admaja Dwi; Prima Zulvarina; Aditya Rachmadi, Mohammad Adnan (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
The study compares the creative thinking skills of vocational high school students who experience Project-Based Learning (PjBL) and Problem-Based Learning (PBL) instructional processes in Software Development subjects. The research was conducted at one of Malang City, Indonesia’s information technology primary vocational high schools (SMK TI). The study used a randomised pretest-posttest control group design experimental research design. The research group was divided into two groups, namely the experimental group (PjBL) and the control group (PBL), where each group consisted of 36 students. The data generated in the study was obtained by conducting a test of creative thinking skills. A comparative analysis of creative thinking skills data in the experimental and control groups was performed using Wilcoxon’s Test. Comparative analysis of pre-test data in the experimental (M=72.36; SD=9.29) and control (M=70.97; SD=9.39) groups resulted in a p-value of more than 0.05. It means there are no differences in pre-test scores between the two groups. In contrast, the p-value for post-test data from the experimental (M=94.02; SD=4.27) and control (M=86.80; SD=6.98) groups was less than 0.01. It means there are no differences in post-test scores between the two groups. Comparative analysis of pre-test and post-test data from the experimental group resulted in z(35)=5.26; p < 0,01; d=3.00. Comparative analysis of pre-test and post-test data from the control group resulted in z(35)=5.26; p < 0,01; d=1.91. According to the findings of the analysis, PjBL and PBL impact students’ creative thinking skills. Compared with effect size, the PjBL effect is more significant than PBL.